The impact of advertising expenditure on the demand for money in Malaysia - Lai, Kim Lin (Universiti Malaysia Sarawak (UNIMAS), 2011)
The main purpose of this study is to determine the characteristic of money demand function in Malaysia by including advertising expenditure as a new variable using annual data over the period of 1978 to 2008. Developed econometric techniques of unit root tests, cointegration tests, vector error-correction modeling and Granger causality test have been employed. The findings verify that the money demand in term of real M2 of Malaysia is significant. The money demand function is stable in the long-run. All of the independent variables include real GDP, saving deposit rate, exchange rate and advertising expenditure can affect the demand for money in the short-run. In addition, the money demand function is fitted excellently with the theoretical concept of money demand.